Spatial Effects and Mechanisms of the Digital Economy on Energy Efficiency: Empirical Findings from China - Rongbin Zhang; Xiaoxiao Wu; Yifei Chen (Energies, 2025)
Energy efficiency plays a vital role in the transition towards carbon neutrality. The rapid rise of the digital economy as an emerging growth engine raises important questions about its capacity to enhance energy efficiency. Understanding this relationship is essential for advancing sustainable development and minimizing carbon emissions. Using spatial Durbin models, mediation models, and panel threshold models, this paper empirically examines the nonlinear impact of digital economy development on energy utilization efficiency, taking Chinese cities as case study areas. This research shows that there is a nonlinear U-shaped relationship between the digital economy and energy efficiency, characterized by initial suppression followed by promotion, while the digital economy’s impact on energy efficiency improvement in surrounding cities shows an inverted U-shaped relationship, demonstrating initial promotion followed by suppression. Heterogeneity studies found that digital economy development in eastern Chinese cities has a significant positive promotional effect on energy efficiency, while cities in central and western regions show a suppressive effect. Mechanism tests indicated that the digital economy enhances energy efficiency by promoting industrial structure upgrading and improving green technological progress. However, its impact is significantly affected by external factors and exhibits threshold effects—only when urban development levels cross specific threshold values can the digital economy generate a positive promotional effect on energy efficiency.